PENGGALIAN POTENSI SISWA MELALUI LITERASI DIGITAL (LAPIS LEGIT) - Sulistyo, Endi (Inisiasi, 2023)
Potential Through Digital Literacy" (LAPIS LEGIT) strategy in the educational context at SD Negeri 3 Giriwarno. Digital literacy is an essential skill in today's digital information era, and this innovative approach is designed to increase the use of technology in the learning process. The LAPIS LEGIT method includes integrating digital literacy into the curriculum, facilitating interactive learning, and increasing student engagement through online resources. This research uses a qualitative approach involving teachers and students at SD Negeri 3 Giriwarno as research subjects. The LAPIS LEGIT intervention is directed at improving students' digital literacy skills, involving project-based learning activities, online collaboration, and the use of technology. During the experimental period, data was collected through digital literacy tests, classroom observations, and student interviews. Findings show a significant increase in students' digital literacy skills, empowerment of students for independent learning, and increased active participation in the learning process. The implementation of LAPIS LEGIT provides a foundation for sustainable skills development in the digital era, preparing students for future challenges. This study also identifies several challenges and recommendations for further development in optimizing student potential through digital literacy. The results of this research contribute to practical and theoretical understanding regarding the integration of digital literacy in the context of formal education. Apart from that, the impact of digital literacy is an increase in the education report card of SD Negeri 3 Giriwarno in 2023 which reached 44%.